2015
DOI: 10.1017/s0033291715000689
|View full text |Cite
|
Sign up to set email alerts
|

Negative cognition, affect, metacognition and dimensions of paranoia in people at ultra-high risk of psychosis: a multi-level modelling analysis

Abstract: n Morrison, A.P. et al. (2015) Negative cognition, affect, metacognition and dimensions of paranoia in people at ultra-high risk of psychosis: a multi-level modelling analysis. Psychological Medicine, 45(12), pp. 2675-2684.There may be differences between this version and the published version. You are advised to consult the publisher's version if you wish to cite from it.http://eprints.gla.ac.uk/109839/ Background. Paranoia is one of the commonest symptoms of psychosis but has rarely been studied in a popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…Patients with the "poor me" condition, however, perceive themselves as undeserved victims of malevolent others (Chadwick, Trower, Juusti-Butler, & Maguire, 2005;Trower & Chadwick, 1995). It is discussed in the current literature that transition from the at-risk state to psychosis is associated with a shift from "bad me" to "poor me" paranoia (Morrison et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Patients with the "poor me" condition, however, perceive themselves as undeserved victims of malevolent others (Chadwick, Trower, Juusti-Butler, & Maguire, 2005;Trower & Chadwick, 1995). It is discussed in the current literature that transition from the at-risk state to psychosis is associated with a shift from "bad me" to "poor me" paranoia (Morrison et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Analyses were conducted using Mplus version 7.31 (Muth en & Muth en, 1998-2015, a latent variable modelling package. We used structural equation models (SEMs) to test the hypotheses, as it allows the assessment of multiple pathways indicating direct and indirect effects, and allows for the simultaneous assessment of the multiple hypotheses.…”
Section: Discussionmentioning
confidence: 99%
“…In the current psychological literature, there is limited research concerning how cognitive and metacognitive variables differentially or jointly influence paranoia. One previous study has investigated the combined role of cognitive and metacognitive factors in relation to paranoia in people at risk of psychosis (Morrison et al ., ). The findings supported several hypotheses of both cognitive and metacognitive models.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Furthermore, impaired metacognitive capacity is correlated with negative symptoms, insight and neurocognitive deficits in schizophrenia (Lysaker et al, 2005;Nicolò et al, 2012). With regard to the latter, other studies have revealed that metacognitive deficits are highly correlated with paranoid ideation and hallucinations in patients with psychosis (Morrison & Wells, 2003;Morrison et al, 2015). Moreover, metacognitive beliefs may be associated with subjective distress in relation to the experience of auditory hallucinations in clinical and non-clinical individuals (Hill, Varese, Jackson, & Linden, 2012), which renders metacognition an interesting cognitive candidate for further exploration in people with at-risk mental states of psychosis (ARMS).…”
Section: Introductionmentioning
confidence: 98%